As condições de trabalho dos(as) assistentes sociais na política de assistência social na administração pública municipal da sub-região oeste da Região Metropolitana de São Paulo - Alves, Vanice Aparecida (2018)
This thesis identifies and analyzes the working conditions and the different forms of intensification and precarization to which the work force of the salaried social workers of the municipal public administration of the western sub-region of the São Paulo Metropolitan Region (RMSP), in particular in the public policy of social assistance. Given that work gains the centrality in social life and expresses the struggle of the working class for better working and living conditions, the strategies of resistance built by workers of the sub-region. It was assumed that the work of the professionals is impacted by the transformations that occurred with the globalization of capital, productive restructuring, reconfiguration of the role of the State, in particular by the reduction of its intervention regarding the social protection of those affected by the development of capital. For the study, bibliographical and documentary research (competition notices) and empirical research were carried out, with the application of questionnaires and interviews with a sample of five (5) social workers working in the social assistance policy in municipalities in the region surveyed. From the interviews, different forms of precariousness and intensification of work were observed, experienced by the majority of the social workers included in the social assistance policy, among them: differentiated contractual relations, unequal rights, low wages, pressure to increase productivity, devaluation of the civil service, lack of material and moral stimuli, absence of job plans, careers and salaries, overwork. Considering also that these conditions of work sicken and weaken the collective organization, either through branch unions or other forms of struggle, such as Suas' Worker Forums. In this context, the path to be taken by all workers is the resumption of struggles and resistance against the barbarism of capital and its state representatives, which precarious and intensify the working and working conditions of the working class